Determination of candesartan and amlodipine using ion pair and cloud point methods - Mohammed Mahmood Abdullah; Eman Thiab Ahmed Al-Samarrai; Mohammed H. Al-Mashhadani; Zamzam Alhuwaymil; Sohad A. Alshareef; Mohamed Bouaziz (Results in Chemistry, 2024)
No communicable diseases are a growing concern in the field of cardiovascular disease, where the use of amlodipine and candesartan, two antihypertensive drugs, has gained significant attention as a commonly used treatment strategy. Bromothymol blue and bromocresol green were used as reagents in UV spectrophotometry to test amlodipine and candesartan. The results obtained were in the dual-ion method, assuming a linear range between 5 and 55 μg mL−1 at pH = 11.5. The optimal dye volume is 0.7 mL. The temperature at which maximum absorption occurred was recorded at 25 °C, with corresponding recovery percentages of 98.2312 % and 102.2449 %. The range of relative standard deviation values is 0.02154–0.096745. The cloud results have a linear range extending from 1 to 55μg mL−1. Thus, at pH = 11, the most appropriate dye volume is 1 mL. The observed recovery rates for this procedure are 98.1045 % and 100.5664 %, respectively. The relative standard deviation (RSD%) results range from 0.013205 % to 0.02427 %. The above spectral estimates were performed with a high level of accuracy, uniformity, and responsiveness. The methods described in this study have been applied in specific contexts.